Foreign Experience in the Development of Classters (Texas Journal of Agriculture and Biological Sciences, 2023)
At present, integration processes are a special driving force for economic development and contribute to the creation and improvement of the competitiveness of enterprises, regions and countries as a whole. Representatives of business, science and government are showing interest in integrated forms of association of economic entities, which is due to the development of scientific and technological progress, competition and the increased importance of intangible assets.